Evolution of an archaeal virus nucleocapsid protein from the CRISPR-associated Cas4 nuclease. Issue 1 (December 2015) - Krupovic, Mart; Cvirkaite-Krupovic, Virginija; Prangishvili, David; Koonin, Eugene
Abstract Many proteins of viruses infecting hyperthermophilic Crenarchaeota have no detectable homologs in current databases, hampering our understanding of viral evolution. We used sensitive database search methods and structural modeling to show that a nucleocapsid protein (TP1) of Thermoproteus tenax virus 1 (TTV1) is a derivative of the Cas4 nuclease, a component of the CRISPR-Cas adaptive immunity system that is encoded also by several archaeal viruses. In TTV1, the Cas4 gene was split into two, with the N-terminal portion becoming TP1, and lost some of the catalytic amino acid residues, apparently resulting in the inactivation of the nuclease. To our knowledge, this is the first described case of exaptation of an enzyme for a virus capsid protein function. Reviewers This article was reviewed by Vivek Anantharaman, Christine Orengo and Mircea Podar. For complete reviews, see the Reviewers' reports section.